It Is Never Too Late to Mend - Reade, Charles, 1814-1884 (Salt Lake City, UT : Project Gutenberg, 2003)
"It Is Never Too Late to Mend" by Charles Reade is a novel published in 1856. A ruthless squire becomes dangerously obsessed with a younger woman and hatches a dark conspiracy to have her lover framed and imprisoned. The story explores themes of injustice and prison reform, inspired by real-life reformer George Hans Hamilton. This gripping tale of villainy and redemption proved so popular it was adapted into multiple stage productions and films across several decades. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/It_Is_Never_Too_Late_to_Mend_(novel)
Release date is 2003-11-01
Produced by James Rusk and David Widger
Keywords: Great Britain -- Social conditions -- 19th century -- Fiction